Tinjauan Hukum Ekonomi Syari’ah Terhadap Pelaku Usaha Pom Mini Di Bengkalis Berdasarkan Undang-Undang Nomor 22 Tahun 2001 Tentang Minyak Dan Gas Bumi - Muhammad Ashsubli; Sukma Mehilda; Ahmad Mas’ari; Deni Al Muzakki (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
This research examines the Review of Sharia Economic Law on Pom Mini business actors based on Law No. 22 of 2001 concerning Oil and Natural Gas in Bengkalis District. The type of research and approach used is qualitative research. The research location is in a village in Bengkalis District. This research data was obtained directly from the Pom Mini business actor Iis Mawardi in Senggoro Village, District. Bengkalis, Julia Fitri in Penampi Village, Kec. Bengkalis and Amri Agustin in Kebun Kapas Village, Kec. Bengkalis, and with Mr. Ilok Diaggoni, S.T. First Expert Tower for the District Trade and Industry Service. Bengkalis. Data collection techniques are carried out using interview, observation and documentation techniques. The results of this research are: 1) Mini Pom business actors are not included in the downstream oil business based on the applicable laws and regulations, the governing law is Law No. 22 of 2001 concerning Oil and Natural Gas as the legal umbrella in the Regulations concerning Oil Management. in Indonesia. 2) Pom Mini business actors do not apply the applicable rules as regulated in Law No. 22 of 2001 concerning Oil and Natural Gas. Even though Pom Mini business actors sell fuel oil to final consumers as gas stations owned by private business entities, Pom Mini business actors are involved in illegal business activities which are not permitted to sell fuel. 3) Based on a review of Sharia Economic Law carried out by researchers and from various sources, the buying and selling practices carried out by business actors at Mini Poms in Kec. Bengkalis is not appropriate according to Islamic law. Because there is ghoror (lack of clarity) in the dosage.